Approximate Periodic Solutions for Oscillatory Phenomena Modelled by Nonlinear Differential Equations - Constantin Bota (Mathematical Problems in Engineering, 2014)
We apply the Fourier-least squares method (FLSM) which allows us to find approximate periodic solutions for a very general class of nonlinear differential equations modelling oscillatory phenomena. We illustrate the accuracy of the method by using several significant examples of nonlinear problems including the cubic Duffing oscillator, the Van der Pol oscillator, and the Jerk equations. The results are compared to those obtained by other methods.